Smart Current Monitoring System with Relay Breaker (ELEKTRIKA- Journal of Electrical Engineering, 2019)
Today, the high usage of electrical home appliances has increased the domestic energy consumption. To control the consumption of domestic energy, various techniques were developed to detect current flow and to measure current consumption. Usually, a current sensor was used as a detection device and then send the data wirelessly to a centre point in the house, which is placed near to the main entrance for monitoring and controlling purposes. Wireless technology can provide better connection and reducing the need for wired connection for all power sockets in a house. The usage of LCD is to display current usage for all electrical home appliances will be more useful especially for a multi-storey house. This smart current monitoring system, will help users to monitor and control their electrical home appliances current consumption. The system will monitor each power sockets and transmit the current usage data wirelessly to a centre point which helps in reducing the time to check all the appliances.